The Use Of Injection Contraceptives Is Associated With Changed In The Menstrual Cycle - Marlinda Marlinda; Sumi Anggraeni (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Latar Belakang Penggunaan alat kontrasepsi bertujuan mencegah terjadinya kehamilan salah satunya dengan metode KB suntik. Kontrasepsi suntik mempunyai permasalahan utama efek samping Pemakaian KB suntik mengalami beberapa permasalahan utama, yaitu gangguan pola menstruasi. Gangguan menstruasi yang terjadi seperti perdarahan bercak, perdarahan irregular, amenorea dan perubahan dalam frekuensi, lama dan jumlah darah yang hilang.Tujuan penelitian untuk mengetahui hubungan penggunaan kontrasepsi suntik dengan perubahan siklus menstruasi pada akseptor KB suntik di Wilayah Kerja Puskesmas Sukaraja Nuban Lampung Timur.Metode penelitian ini menggunakan desain survey analitik dengan pendekatan cross sectional. Jumlah populasi 643, didapat 97 sampel dengan tehnik quota sampling. Instrumen yang dipakai kuesioner perubahan siklus mentruasi dan rekam medik pengunaan KB. Analisis data yang menggunakan uji chi square. Hasil penelitian diketahui bahwa responden yang menggunakan KB suntik 3 bulan (57,7%), dan mengalami perubahan siklus mestruasi (56,7%).KesimpulanSaran Diketahui ada hubungan penggunaan kontrasepsi suntik dengan perubahan siklus menstruasi pada akseptor KB suntik dengan nilai p-value = 0.000 < 0.05 Diharapkan tenaga kesehatan dapat memebri informasi tentang efek samping pemakaian KB suntik 3 bulan, ada hubungan antara lama pemakaian KB suntik 3 bulan dengan gangguan menstruasi, dan menganjurkan klien jika merasa ada gangguan terhadap pemakaian KB suntik 3 bulan untuk mengganti metode kontrasepsi lainnya Kata Kunci : KB Suntik, Perubahan Siklus Mestruasi ABSTRACT Background Contraception is an effort to prevent pregnancy from occurring asexpected to reduce the high birth rate. One type of contraceptive that is the choice of many women of childbearing age today is injecting birth control because it is easy, cheap and many suitable. Injection birth control with the use of estrogen and or progesterone hormones will inhibit the menstrual cycle by affecting the work of the reproductive organs of the uterus and ovaries. This is what is sometimes not realized by the acceptor of birth control, especially when using injection contraceptives in the long term. The impact that is often complained about by acceptors of birth control is an irregular menstrual cycle. The purpose of the study was to determine the relationship between the use of injection contraceptives and changes in the menstrual cycle in the acceptor of injection birth control. This research method uses an analytical survey design with a cross-sectional approach. The total population was 643, 97 samples were obtained with quota sampling techniques. The instruments used are in the form of questionnaires about changes in the mentruation cycle and medical records of the use of kb. Data analysis using chi square test. The results of the study found that respondents partially used injection birth control for 3 months (57.7%), and experienced changes in the mestruation cycle (56.7%).Conclusion It is known that there is a relationship between the use of injection contraceptives and changes in the menstrual cycle in the acceptor of injection birth control with a p-value = 0.000 < 0.05Sugesstion It is expected that health workers can provide information about the side effects of using injection birth control and recommend clients if they feel there is a disturbance in the use of injection birth control for 3 months to replace other contraceptive methods Keywords: Mestruation Cycle Changes, Injection KB